Study on occurrence of myiasis in different species of animals at Babuganj Upazilla of Barishal district in Bangladesh - Nini, Lamyea Farzana; Matubber, Bidyut; Arif, Md Atikuzzaman; Talukder, Milton (Asian Journal of Medical and Biological Research, 2022)
Myiasis is a common insect borne surgical problem of animals in Bangladesh. The present study was conducted to find out the occurrence in relation to various epidemiological factors in various species of animals at Upazilla Veterinary Hospital, Babugonj, Barishal, during the period of study from December 2020 to April 2021. Myiatic cases were identified by clinical examination with presence of maggot larvae in the affected regions. Questionnaire was used to collect data on species, sex, season, affected body region, age of animals. A total of 110 cases were recorded myiasis positive among 500 examined animals during the period of study. The overall occurrence of myiasis in different species of animals was 22%. Female animal of cattle, sheep, goat and buffalo were highly affected (63.63%) than male (36.36%). Goats were highly infected with myiasis followed by cattle, sheep and buffalo (45.45%, 22.72%, 18.18% and 13.63%, respectively). Myiasis frequently occurred in March and April (54.54%).The myiasis infestation rate was higher in local (68.18%) breed of cattle (local: 13; cross: 12), goat (local: 27; cross: 23), sheep (local: 20), buffalo (local: 15) than the cross (31.82%)breed. The <6 months (45.45%) aged animals were mostly affected followed by 6 months to 2 years (31.82%), and >2 years (22.73%) groups. The highly affected body region was navel (20%) followed by leg (18.18%), vulva lips (16.36%), hoof (15.45%), skin (12.73%), ear (9.09%) and neck (8.18%), respectively. This study will provide valuable information for future research on myiasis infestation in animals and impart the idea of maggot wound management. Asian J. Med. Biol. Res. 2022, 8 (1), 24-29